Design and synthesis of n-[3-(3-oxoprop-1-yn-1-yl) phenyl] benzene sulfonamide: a highly active antimicrobial compound - Cabezas Pizarro, Jorge A. (2019)
The synthesis of the highly active compound N-[3-(3-oxoprop-1-yn-1-yl)phenyl] benzene sulfonamide was performed and its activity against Gram (+), Gram (-), mold and yeast was determined.